First record of Dosinia prostrata (Linnaeus, 1758) (Bivalvia: Veneridae) from the Iraqi coast - Naser, Murtada; Yasser, Amaal; Abdul-Sahib, Ibtisam; Abdul-Sahib, Azhar; Auda, Nabaa (Journal of Fauna Biodiversity, 2024)
The objective of this study is to collect novel data on the distribution of bivalves along the Iraqi coastline. Between 2020 and 2021, a new record of the bivalve Dosinia prostrata (Linnaeus, 1758) was discovered along the Iraqi coast in the northwestern Persian-Arabian Gulf.